1998
DOI: 10.1038/sj.bmt.1701380
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation and cyclophosphamide is a conditioning regimen for unrelated bone marrow transplantation in a patient with chronic myelogenous leukemia and renal failure on hemodialysis

Abstract: Summary:Five years after the diagnosis of Ph chromosome-positive chronic myeloid leukemia (CML) a 31-year-old patient developed malignant nephrosclerosis with renal failure. He then underwent an allogeneic unrelated BMT in first chronic phase CML. The preparative regimen consisted of fractionated total body irradiation (TBI) and cyclophosphamide (CY). We studied the pharmacokinetics of cyclophosphamide on hemodialysis and compared clinical parameters including time to engraftment and toxicity with parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Allogeneic transplantation in patients on chronic dialysis has been reported. 47,48 Ordinarily, we do not consider it except in rare cases of a young highly motivated individual who has a very poor-prognosis genotype.…”
mentioning
confidence: 99%
“…Allogeneic transplantation in patients on chronic dialysis has been reported. 47,48 Ordinarily, we do not consider it except in rare cases of a young highly motivated individual who has a very poor-prognosis genotype.…”
mentioning
confidence: 99%
“…Therefore, documented experiences in this setting remain extremely limited. Indeed, to the best of our knowledge, only four case reports have been published, demonstrating the feasibility of allogenic HSCT in carefully selected patients [114][115][116][117]. Reduced-intensity conditioning allogeneic HSCT has been proposed as an alternative transplantation option to reduce HSCT-related toxicity.…”
Section: High-dose Chemotherapy and Stem Cell Transplantation In Renal mentioning
confidence: 99%
“…However, data are controversial. Minimal eVects of renal dysfunction upon cyclophosphamide AUC have been reported [8,11,12], while others have shown an elevated AUC in those with impaired renal function [9,10,13]. A report in an anephric child indicated that oV haemodialysis clearance of cyclophosphamide was similar to cyclophosphamide clearance in children with normal renal function [14].…”
Section: Introductionmentioning
confidence: 99%
“…Scarce information is available about the pharmacokinetics of (high dose) cyclophosphamide and thiotepa in patients with renal insuYciency. Earlier studies have described the pharmacokinetics of cyclophosphamide in adults with renal dysfunction receiving either standard dose [7][8][9][10][11] or myeloablative doses of cyclophosphamide [12,13]. However, data are controversial.…”
Section: Introductionmentioning
confidence: 99%